2023
DOI: 10.3390/universe9070312
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Spectral Energy Distributions Emanating from Regular Galactic XRBs

Abstract: X-ray binary systems (XRBs) exhibit similar dynamics and multimessenger emission mechanisms to active galactic nuclei (AGNs) with the benefit of shorter time scaling. Those systems produce rich spectral energy distributions (SEDs) ranging from the radio band to the very high energy gamma rays. The emission origin varies between the system’s accretion disk (X-rays) to the corona and, most notably, to the two twin plasma ejections (jets) that often meet the interstellar medium forming highly observable radio lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…The dependence of the jet gamma-ray photon absorption on the disk's geometry and radiative efficiency is better illustrated in Refs. [39,40]. In those works, we conducted similar calculations which are, in the present work, extended by applications on two additional X-ray binaries, namely, GRO J1655-40 and LMC X-1.…”
Section: Photon Annihilation In the X-ray Binary Environmentmentioning
confidence: 84%
See 2 more Smart Citations
“…The dependence of the jet gamma-ray photon absorption on the disk's geometry and radiative efficiency is better illustrated in Refs. [39,40]. In those works, we conducted similar calculations which are, in the present work, extended by applications on two additional X-ray binaries, namely, GRO J1655-40 and LMC X-1.…”
Section: Photon Annihilation In the X-ray Binary Environmentmentioning
confidence: 84%
“…In previous works, we assumed purely hadronic jets focusing on multiple independent acceleration zones [39], or we studied primarily the lepton-induced mechanisms investigating the dependence on the jet parameterization [40]. In both cases, priority was given only to the multi-wavelength photon emission from X-ray binary systems and not the production of neutrinos, which is included in this work.…”
Section: Model Calculations For the Astrophysical Outflows From X-ray...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the proposed mechanism [16], as the mass accretion rate increases, cold clumps can form within the hot accretion flow due to recondensation. Another component that is missing in this classical picture is the collimated jet [17], which can be a significant source of the X-ray emission in the hard state, and it is shown to dominate the X-ray emission in the quiescent state [18]. Recent studies showed that the jet contribution itself depends on the BH spin [19].…”
Section: Introductionmentioning
confidence: 99%